Up-Conversion Luminescence and C-Band Laser in Er3+-Doped Fluorozirconate Glass Microsphere Resonator - Haiyan Zhao; Xin Wang; Ruicong Wang; Angzhen Li; Wenhao Li; Elfed Lewis; Yaxian Fan; Shijie Jia; Shunbin Wang; Pengfei Wang (IEEE Photonics Journal, 2019)
Up-conversion luminescence and C-band microsphere laser output is reported for an Er3+-doped ZrF4-BaF2-YF3-AlF3 (ZBYA) fluorozirconate glass microsphere. The microsphere was fabricated by heating a ZBYA glass filament using a CO2 laser beam. The fabrication process accurately and repeatably produces microspheres of 68 μm diameter. The input and output laser light was coupled to the microsphere using a tapered optical fiber. The coupling position between the tapered fiber and microsphere was adjusted using a sophisticated three-dimensional translation stage. The up-conversion luminescence emission, single-mode and multi-mode laser at C-band (1530 to 1565 nm) were observed when pumped using a 980 nm laser.